Characterization of sakA gene from pathogenic dimorphic fungus Penicillium marneffei - Nimmanee P. (Urban und Fischer Verlag GmbH und Co. KG, 2015)
© 2014 Elsevier GmbH. Eukaryotes utilize stress activated protein kinase (SAPK) pathways to adapt to environmental stress, including heat, osmotic, oxidative or nutrient stresses. Penicillium marneffei (. Talaromyces marneffei), the dimorphic pathogenic fungus that can cause disseminated mycosis in HIV-infected patients, has to encounter various types of stresses both outside and inside host cells. However, the strategies used by this fungus in response to these stresses are still unclear. In this report, the stress-activated kinase (. sakA) gene of P. marneffei was characterized and the roles of this gene on various stress conditions were studied. The sakA gene deletion mutant was constructed using the split marker method. The phenotypes and sensitivities to varieties of stresses, including osmotic, oxidative, heat and cell wall stresses of the deletion mutant were compared with the wild type and the sakA complemented strains. Results demonstrated that the P. marneffei sakA gene encoded a putative protein containing TXY phosphorylation lip found in the stress high osmolarity glycerol 1 (Hog1)/Spc1/p38 MAPK family, and that this gene was involved not only in tolerance against oxidative and heat stresses, but also played a role in asexual development, chitin deposition, yeast cell generation in vitro and survival inside mouse and human macrophages.